Virologica Sinica - Zhongguo ke xue yuan. Wuhan bing du yan jiu suo (Wuhan Institute of Virology, Chinese Academy of Sciences, co-published with Springer-VerlagSpringer, 2007)
"New research results in theory and application of virology in disease control and prevention, manufacture of medicine, plant protection, veterinary medicine, live-stock husbandry, aquatic production, and fermentation industry. Topics covered include insect viruses, animal viruses, medical viruses, veterinary viruses, plant viruses, aquatic biologic viruses, phages and viroids, as well as the new techniques methods, the most recent advances of virology in China and abroad."
Keywords: Virology : Technique : Periodicals; Virus diseases : Treatment : Research : Periodicals; Virology; Virology : Technique; Viruses : Research; Viruses : Research : Periodicals; Virology : China : Periodicals; Virus diseases : Prevention : Research : Periodicals; China